2020
DOI: 10.1038/s41598-020-75242-y
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo mechanical sealing properties and toxicity of a bioadhesive patch as sealing system for fetal membrane iatrogenic defects

Abstract: Preterm prelabor rupture of membranes (PPROM) is the most frequent complication of fetal surgery. Strategies to seal the membrane defect created by fetoscopy aiming to reduce the occurrence of PPROM have been attempted with little success. The objective of this study was to evaluate the ex-vivo mechanical sealing properties and toxicity of four different bioadhesives integrated in semi-rigid patches for fetal membranes. We performed and ex-vivo study using term human fetal membranes to compare the four integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…A variety of fetal membrane plugs [6,[12][13][14][15][16][17][18][19], tissue sealants [14,17,28,[91][92][93][94][95][96][97], adhesive patches [17,[23][24][25], and membrane welding techniques [98] have been developed in preclinical models to seal punctured or ruptured fetal membranes (summarized in Table 1). Collagen/gelatin plugs are one of the few techniques trialed in humans during fetoscopy; however, there is limited evidence to suggest they reduce the iPPROM compared to leaving the membranes unsealed [20][21][22].…”
Section: Fetal Membrane Plugs Glues and Patchesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of fetal membrane plugs [6,[12][13][14][15][16][17][18][19], tissue sealants [14,17,28,[91][92][93][94][95][96][97], adhesive patches [17,[23][24][25], and membrane welding techniques [98] have been developed in preclinical models to seal punctured or ruptured fetal membranes (summarized in Table 1). Collagen/gelatin plugs are one of the few techniques trialed in humans during fetoscopy; however, there is limited evidence to suggest they reduce the iPPROM compared to leaving the membranes unsealed [20][21][22].…”
Section: Fetal Membrane Plugs Glues and Patchesmentioning
confidence: 99%
“…Techniques to reduce iPPROM after fetoscopy have been investigated extensively in humans and preclinical models (summarized in Table 1) [6]. Efforts have mainly focused on minimizing membrane damage by reducing the number and diameter of fetoscopic ports and using plugs (gelatin or collagen), glues, patches, or sutures to seal the holes left in membranes after surgery [3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. More recently, heated and humidified CO 2 gas has been used for amniotic insufflation to prevent the fetal membranes dehydrating and becoming prone to rupture after surgery [4,27,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The notion that iatrogenic damages were unfortunate but largely unavoidable adverse consequences of necessary treatment was present in 13 of the 31 articles (41.9%). All of these articles described medical care and they presented iatrogenic damages as “potentially life-threatening complications” ( Ruffino et al, 2020 , p. 1) of necessary surgeries, a “vessel injury” sustained during tumor resection ( Nariai et al, 2020 ), an “adverse clinical condition” ( Gomes et al, 2017 , p. 511) that results from the provision of many types of care, an “unsolved drawback” of revolutionary new investigations ( Micheletti et al, 2020 , p. 1) and as “another pattern of vascular trauma” similar to blunt or penetrating traumas that might occur in the community ( Lui et al, 2020 , p. 5). Sharpe and Faden (1998) identify this tendency to describe iatrogenesis as an unavoidable consequence of progress as a “utilitarian understanding” (p. 64).…”
Section: Resultsmentioning
confidence: 99%
“…Engels et al reported that a collagen plug imbued with fibrinogen and plasma reduced amniotic fluid leakage in an ex vivo set-up approximately 35% better than a control plug [ 25 ]. Other studies used polymer based patches like Tissuepatch in vivo [ 26 ], bioadhesive-coated silicone patches [ 27 ] and fetal membrane patches ex vivo [ 28 ]. Alternative techniques included the use of sealants and tissue adhesives, such as Duraseal in rabbits [ 26 ], fibrin glue and mussel mimetic tissue adhesive both in vivo and ex vivo [ [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%